2013
DOI: 10.1177/1532673x12473503
|View full text |Cite
|
Sign up to set email alerts
|

The (Dis)Connection Between Political Culture and External Efficacy

Abstract: Theories of political culture have traditionally been based on how the mass public views the role of government, yet scholars have rarely studied this issue. Using American National Election Studies(ANES) data from 1952 to 2008, I track cultural changes in external efficacy, a measure of the public’s beliefs about government responsiveness. The aggregate- and individual-level results indicate that external efficacy varied across political cultures until around 1980, when the differences dissipated. These findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Similarly, Weston-Cox et al, 2012 andLi &Elligers, 2014 connected state agency staffing levels (including non-environmental agencies) with funding. Education attainment has long been recognized as correlated to environmental awareness (Konisky, 2011;Koven & Mausolff, 2002;and Chamberlain, 2013) and so, by extension, to the robustness of state environmental agency funding. The independent variable Performance, a measure of overall state bureaucratic effectiveness, is based largely on infrastructure and financial management (Barrett & Greene, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Weston-Cox et al, 2012 andLi &Elligers, 2014 connected state agency staffing levels (including non-environmental agencies) with funding. Education attainment has long been recognized as correlated to environmental awareness (Konisky, 2011;Koven & Mausolff, 2002;and Chamberlain, 2013) and so, by extension, to the robustness of state environmental agency funding. The independent variable Performance, a measure of overall state bureaucratic effectiveness, is based largely on infrastructure and financial management (Barrett & Greene, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Non-economic factors also have been used regularly to assess the presence or strength of relationships between state environmental commitment and constituent characteristics. Educational attainment (Koven & Mausolff, 2002;Konisky, 2011;Chamberlain, 2013), advocacy group activity (Hays et al, 1996) and moral or cultural beliefs (Heckman, 2012;Olive et al, 2012) have been shown to be correlated, either positively or negatively, with state environmental policy development and outcomes.…”
Section: Study Basismentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents scoring 75 after 1988 were coded as 1. See Chamberlain (2013) for an example of the external political efficacy index coded and used in this way. 10 Other measures of political polarization were included in previous models but were not used because if high collinearity between polarization and income inequality.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Political efficacy has been conceptualized as two discrete constructs: internal and external (Chamberlain 2013; see also Dyck and Lascher 2009;Pingree 2011). Internal efficacy has been defined as "beliefs about one's own competence to understand, and to participate effectively in, politics," while external efficacy "refer[s] to beliefs about the responsiveness of governmental authorities and institutions to citizen demands" , 1407-1408, relying on Lane 1959.…”
Section: Measuring Interest and Efficacymentioning
confidence: 99%